International organisation law as a political instrument and indonesia's experience in case studies - Darajatiula, Rizi; Astriani, Shelly; Loviyanti, Febby; Tarigan, Cherin; Pulungan, M Rifky; Tanjung , Indra (Institute Of computer Science (IOCS), 2024)
International law in its basic concept is meant as a legal framework that serves the people of a country. International law determines what is right and what is wrong, also regulates how countries behave towards each other, and provides sanctions. Of course, this is a description of international law. as understood in the classroom. In fact, international law is often used as a political instrument by states. This law can be a tool for pressure, an instrument for intervening in other countries in household affairs without being considered a violation and can also be used to justify state actions. .This article will explain how countries have used international law in Indonesia as a political instrument and how Indonesia has used international law to further its national policies. Key Word : International law, National Policy, State